Academics' Perceptions of the Effects of Globalization on Turkish Foundation University Policies - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2012)
While western countries are coping with the challenges arising from globalization, a key question being asked is whether the same or similar challenges are dominating a country that is trying to become westernized but regarded as a Muslim-European-Asian country. This study, therefore, attempts to explore academics' perceptions regarding the impact of the globalization process on higher education institutions in a country like Turkey that has a different culture, history, language, and so on, compared to other European communities. Analyses are based on qualitative interviews with 19 academics working at two foundation universities in Turkey. Findings of the study reveal that globalization has affected university policies in the areas of goals, marketing policies and the professional development opportunities provided for academics.
Keywords: Globalization; academics; university policy